Historical spread routes of wild walnuts in Central Asia shaped by man-made and nature - Li, Xuerong; Wang, Xiyong; Zhang, Daoyuan; Huang, Junhua; Shi, Wei; Wang, Jiancheng (Frontiers in Plant Science, 2024)
Walnuts have substantial economic value and are of significant interest being a wild-cultivated species. The study has re-sequenced the entire genome of the wild walnut, aligning it with the walnut reference genome, to identify 2,021,717 single nucleotide polymorphisms (SNPs). These were used to examine the genetics of 130 wild walnut samples collected from three countries. Utilizing structural and principal component analysis, the walnut samples from Central Asia were classified into four populations: Ili ah in Xinjiang (I), Dushanbe region in Tajikistan (II), Sary-Chelek, Arslanbob in Kara-Alma regions of Kyrgyzstan (III), and Kok-Tundy region of Kyrgyzstan (IV). The 4 groups showed large differences in nucleotide diversity, population differentiation, and linkage disequilibrium decay, as well as gene flow among them. The present geographic distribution of these populations does not align with the genetic distribution pattern as the populations of Central Asian wild walnuts have experienced similar population dynamics in the past, i.e., the highest effective population size at ca. 6 Ma, two sharp population declines at 6 and 0.2 Ma, and convergence at ca. 0.2 Ma. The genetic distribution patterns are better explained by human activity, notably through archaeological findings of walnut use and the influence of the Silk Road, rather than by current geographic distributions.